Comparison of non-invasive assessment for pulmonary vascular indices by two-dimensional echocardiography and cardiac computed tomography angiography with conventional catheter angiocardiography in unrepaired Tetralogy of Fallot physiology patients weighing more than 10 kg: a retrospective analysis. (3rd May 2022) - Kumar, Amarendu; Sahu, Ankit Kumar; Goel, Pravin K; Jain, Neeraj; Garg, Naveen; Khanna, Roopali; Kumar, Sudeep; Tewari, Satyendra; Kapoor, Aditya
Abstract: Aims: Assessment of pulmonary vascular dimensions (PVDs) in Tetralogy of Fallot (TOF) is an integral part of planning transcatheter and surgical interventions. We sought to examine the reliability and correlation of echocardiography (ECHO) and computed tomography angiography (CTA) measurements with those obtained by cardiac catheterization and angiography (CCA). Methods and results: Tetralogy of Fallot physiology patients undergoing ECHO, CTA, and CCA within a month prior to surgical correction during 2018–2020 were retrospectively enrolled. Indexed diameter of pulmonary annulus (iPAnn), indexed right pulmonary artery (iRPA), indexed left pulmonary artery (iLPA) and indexed descending aorta (iDA) were measured using ECHO and CTA followed by derivation of Nakata index (NI), McGoon's ratio (MGR), ratio of predicted peak right ventricular (RV) and left ventricular (LV) pressures (pRV/pLV) and Z -scores. Comparison with CCA-derived measurements was made and correlational equations were subsequently deduced. Pulmonary vascular dimensions for 54 patients with mean age of 15.5 ± 9.3 years (range: 3–34 years) were analysed. Computed tomography angiography and CCA measurements for iPAnn, iRPA, NI, MGR, pRV/pLV, and Z -score were comparable with each other while ECHO parameters were significantly lower than CCA. However, iLPA diameter was significantly underestimated by ECHO and overestimated by CTA. Correlational analysis showed stronger correlation between CTA- and CCA-derived PVD as against ECHO measurements except for iDA, pRV/pLV, and Z -score. Conclusions: For unrepaired TOF physiology patients weighing more than 10 kg, CTA-acquired PVD are reliable and comparable with CCA except for DA for which ECHO is non-inferior. Non-invasive modalities though are inferior to CCA for LPA sizing. Utilizing derived equations, precise estimation of PVD can be carried out using non-invasive tools. Graphical Abstract: Graphical Abstract